Plate Settlement: Determination of Fouling Organisms in Brunei - Hjh Zuliza Hj Jolkifli; Ranimah H.A Wahab (Universitas Gadjah Mada, 2018)
Shipping is considered a primary vector of biological invasion. Hull fouling is recognized as one of the common vectors involved in the translocation of marine pests that may have deleterious impacts to ecology and economy. In an effort to understand the fouling communities within Brunei waters and as an early attempt to obtain baseline data, PVC plates were deployed at a depth of 1 meter, checked for taxa composition and replaced with new plates monthly and quarterly over a period of one year. The Caribbean bivalve Mytilopsis sallei was absent throughout the period of study, and plates were mainly colonized by native fouling species and silt. Nevertheless, further verification on the absence of Invasive Alien Species (IAS) is still required. This study summarizes the improved methods of analysis for better control and management in order to impede the incursion or invasion of undesirable species.